동시 발생한 갑상선 유두암과 수질암 - 최재영(Jaeyoung Choi); 김윤석(Yoonseok Kim); 김정훈(Jeong-hoon Kim) (Annals of surgical treatment and research, 2007)
We report here on a rare case of concurrent papillary thyroid carcinoma and medullary thyroid carcinoma on each of the lobes of the thyroid gland. A 43-year-old female presented with a one-week history of throat discomfort. A neck ultrasonogram (US) was done, along with fine needle aspiration biopsy (FNAB) of the left thyroid nodule, and the results showed papillary cancer. This patient underwent total thyroidectomy and central compartment neck dissection. The pathologic diagnosis of the nodule at the left lobe of the thyroid was papillary thyroid carcinoma (PTC) and the right thyroid nodule was medullary thyroid carcinoma (MTC). (J Korean Surg Soc 2007;73:250-253) KCI Citation Count: 0